Instructional design fieldbook - Wolfe-Burleson, Kathryn A.; Herron, Josh; Zimmerman, Aaron Samuel, 1982- (Emerald Publishing Limited : Information Age Publishing, Inc., 2022)
"From a field developed out of the need to train military personnel at scale to its current role in enabling virtual learning and training experiences, instructional design has developed into a complex, multifaceted discipline. The modern instructional design process goes by many names (e.g., learning experience design, learning engineering, training and development, organizational development) and continues to adapt with continual changes in society and skill development needs. From mobile to remote learning as well as online and traditional classrooms, instructional designers are faced with meeting the learner where they are to design authentic and engaging learning experiences. Additionally, learning development needs have expanded outside of formal learning into professional development, on the job training, and continuous learning. The Instructional Design Fieldbook provides real-world case studies for those in the field, or entering the field, into many of the areas and situations that instructional designers (IDs) face. This text speaks to the multifaceted discipline of instructional design and supplies resources for those entering or transitioning into the field, specifically K12 education, higher education, corporate, healthcare, entertainment, and nonprofit/government sectors. Case studies and related materials will steer instructional design and learning technology students and those entering or transitioning into specific areas of instructional design towards a genuine understanding of what it is to be an instructional designer"--